Analysis Foundation Planning Bored Pile Pier P1 Sta 8+442 Project Toll Road Depok – Antasari Section Ii - Fadhillah Arizky Noor; Resi Aseanto (NAROTAMA UNIVERSITY, Indonesia, 2021)
The purpose of this study is to plan a construction stability of the upper and lower structures in the construction of the Depok - Antasari toll road section II, especially in the planning of a foundation. The foundation used in pier p1 is the foundation in the bored pile type. In planning the foundation, it is necessary to take into account the load force acting on the pier, the bearing capacity of the foundation piles, and the settlement. Analysis of bridge loading calculation (Badan Standarisasi Nasional, 2008) and (Badan Standarisasi Nasional, 2008) using a software program, namely SAP 2000 v.20. The purpose of this loading analysis is to find the value of the pier bearing reaction force to the working forces, both from the fixed load force and the environmental action load. In order for the purpose of this study to be achieved, literature studies from various sources both from the Indonesian National Standard and various other sources discuss the planning of foundation calculations, namely the AASHTO, Kullhawy, Vesic and Reese Wright methods. The results of this study explain that it must be paid attention to planning a foundation that meets the parameters and structures that are safe against earthquakes and other loads, it is also necessary to take into account the momentary reaction force, bearing capacity of the pile and land subsidence according to national standards.